Analysis of Image Capture Techniques in Journalistic Photos of the Cik Puan Market Fire Disaster in Pekanbaru Online Media - Suardi, Suardi (Newinera Publisher, 2024)
Journalistic photos play an important role in conveying information to the public in a visual way. Photos taken in disaster situations, such as fires, have a special role because in addition to recording events, they also contain social and humanitarian values. This study aims to analyze the techniques of capturing images in journalistic photos that capture the Cik Puan Market fire disaster in Pekanbaru, as published by TribunPekanbaru.com media. The study used a qualitative descriptive method with a non-participant observation approach. The results of the study showed that the photos used successfully captured the emotions of the victims, the condition of the burned market, and the extinguishing efforts made. Journalistic photography techniques such as framing, angle, and timing greatly influence the message in each image. TribunPekanbaru.com media consistently presents photos that have high news value without the applicable journalistic code of ethics.